The Urgency Of Press FreedomRelated To Conflict Of Norms Viewed From The Perspective Of Dignified Justice - Jonianto Silalahi; Teguh Prasetyo; Budiarsih; Tomy Michael (PT. Anagata Sembagi Education, 2024)
The Unitary State of the Republic of Indonesia (NKRI) as a legal state based on the Almighty God has an obligation to protect the rights of its citizens, including press freedom. Press freedom, as the fourth pillar of democracy, is guaranteed by the 1945 Constitution and Law of the Republic of Indonesia Number 40 of 1999 on the Press, which guarantees the right to obtain and disseminate information. However, recent laws such as Law No. 19 of 2016 on Electronic Information and Transactions (ITE Law) and its revision in Law No. 1 of 2024, along with provisions in the Criminal Code, pose potential norm conflicts with press freedom. Articles in the ITE Law are often used to curb press freedom, contrary to the Press Law which provides legal protection for journalistic activities. This research uses a normative legal method to analyze the conflict of norms between the ITE Law, the Criminal Code, and the Press Law. Through this approach, the research examines how legal principles such as Lex Superior Derogat Legi Inferiori and Lex Specialis Derogat Legi Generalis can be applied to resolve conflicts and ensure effective protection of press freedom within the Indonesian legal framework